Rantai Pasok dan Efisiensi Pemasaran Cabai Keriting di Kelurahan Bukit Biru: Red Chili Supplay Chain Analisys and Marketing Efficiency in Bukit Biru Sub District - Drianti, Astik; Damayanti, Arista; Sari, Ira Oktaviani Lita (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2024)
Red chilii is a commodity that is often sought after by the community to be used as a complementary spice for cooking or is often used to make the color of dishes bright and inviting to eat. Increasing population development has an effect on the need for curly chili in the community. The Aimed of this study was to determine the supply chain of curly chili in the Urban Bukit Biru. To find out the amount of marketing costs, marketing margins, and share margins on each channel. To find out the marketing efficiency of curly chili in Urban Bukit Biru Sub-district Tenggarong. Data collection was carried out by direct interviews with respondents using a list of research questionnaires and direct field observations. The results showed that there were 2 marketing channels in the curly chili supply chain in Urban Bukit Biru Sub-district Tenggarong. The lowest marketing costs are in channel 1 which is IDR 681/Kg, then the highest marketing margin is on channel 2, which is IDR 13,000/Kg and the highest margin share is on channel 1, which is 94.32%. The results of the marketing efficiency calculation stated that channel 1 was efficient and channel 2 was not yet efficient. Key Words : Marketing efficiency, Red chili, Supplay chain